Transformation of the Preservation of the Rejang Sutri Dance in Batuan Village: A Literature Analysis Through YouTube Media - Mihrayanti, Kadek Dwikaputri Sila; Dewi, Ni Luh Yulyana (Pasundan Social Science Development, 2025)
The transformation of media from oral traditions and live performances to digital documentation has created a new space for cultural preservation in the modern era. This shift demonstrates how digital technology can bridge local traditions with the needs of an increasingly connected global society. This literature review analyzes the transformation of traditional dance preservation through digital media, with a focus on the use of YouTube in preserving the Rejang Sutri Dance in Batuan Village, Bali. This study aims to synthesize empirical findings and theoretical frameworks from national and international research conducted between 2018 and 2025. Using a qualitative literature review methodUsing Jenkins' (2006) Media Convergence theory, which encompasses indicators of media convergence, participatory culture, and collective intelligence, this study explores various approaches, including digital documentation, documentary film, social media engagement, and digital narratives, as tools for cultural preservation. Key findings indicate that YouTube plays a significant role in documenting, promoting, and educating the public about the Rejang Sutri Dance. Digital media enables this sacred dance to reach younger generations and global audiences, and opens up spaces for creative collaboration without diminishing traditional values. However, challenges identified include varying content quality, unequal access to technology, and the risk of reducing sacred meanings due to cultural commodification. The implications of this study emphasize the need for inclusive, adaptive, and collaborative information technology-based preservation strategies, as well as the importance of youth engagement as drivers of cultural participation. Future research should explore sustainable models for digital cultural preservation and evaluate the long-term socio-cultural impacts of these evolving practices. This study contributes to the growing body of knowledge on the intersection of culture, technology, and education, providing insights for academics, cultural institutions, and community leaders involved in the preservation of intangible cultural heritage.